UAE Police Administrative Employee Innovative Behavior: The Integration of Knowledge Sharing and Leadership - Naser Abdulqawi Gharama, Abdulla; S.A. Khalifa, Gamal; Hamoud Al-Shibami, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to identify the relationship among strategic leadership (SL), knowledge-oriented leadership (KOL), and knowledge sharing (KS) toward employee innovative behavior (EIB) in UAE police administration. A quantitative research approach has been conducted for the study, and a survey-based method has followed in the research, and a distributed questionnaire among employees to collect data. The questionnaire has developed into a five-point Likert scale, and structured questionnaires were distributed among UAE police administration employees. This study finding has shown separate direct and indirect relationship influences among variables. SL and KOL influence on KS toward EIB. The influence of SL and KOL on KS has significantly increased, and KS plays a role as a mediator of SL, KOL, and EIB. These relationships are supported according to the result that is shown in the hypotheses.